2004
DOI: 10.1523/jneurosci.2836-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Regulation of Retinal Growth Cone Filopodial Dynamics Is Mediated through Actin Depolymerizing Factor/Cofilin

Abstract: The molecular mechanisms by which neurotrophins regulate growth cone motility are not well understood. This study investigated the signaling involved in transducing BDNF-induced increases of filopodial dynamics. Our results indicate that BDNF regulates filopodial length and number through a Rho kinase-dependent mechanism. Additionally, actin depolymerizing factor (ADF)/cofilin activity is necessary and sufficient to transduce the effects of BDNF. Our data indicate that activation of ADF/cofilin mimics the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 75 publications
(105 reference statements)
9
93
0
Order By: Relevance
“…BDNF acts via Rho GTPases to regulate the assembly of the actin cytoskeleton in developing neurons (Ozdinler and Erzurumlu, 2001;Gehler et al, 2004;Miyamoto et al, 2006), and there is previous evidence that aspects of these signaling pathways are retained into adulthood in hippocampus . These observations point to BDNF as a logical candidate for a treatment to offset the problems in spine reorganization hypothesized to arise from the fragile X mutation.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF acts via Rho GTPases to regulate the assembly of the actin cytoskeleton in developing neurons (Ozdinler and Erzurumlu, 2001;Gehler et al, 2004;Miyamoto et al, 2006), and there is previous evidence that aspects of these signaling pathways are retained into adulthood in hippocampus . These observations point to BDNF as a logical candidate for a treatment to offset the problems in spine reorganization hypothesized to arise from the fragile X mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Results reported in this study are in agreement with Chan et al (56), who showed epidermal growth factor stimulation up-regulates cofilin severing activity in MTLn3 cells lysates, and the work of Bailly et al (77), who demonstrated a decrease in filament length in ultrastructural studies of epidermal growth factor-treated cells. Gehler et al (78) recently reported that BDNF promoted activation of ADF/cofilin by dephosphorylating ADF/cofilin. The severing activity of ADF/cofilin was necessary to mediate the effects of BDNF because a nonsevering mutant of ADF/cofilin blocked the effects of BDNF on filopodial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…JNK has been reported to promote PDGF-BB-induced dephosphorylation of cofilin (37). The dephosphorylated form of cofilin is active and can influence filopodial dynamics (38,39) and neurite outgrowth (40 -42) by regulating F-actin dynamics. To investigate a more direct mechanism for the effect of JIP3 on axon elongation, we performed immunofluorescence analysis of the levels of phosphorylated cofilin (p-cofilin) in hippocampal neurons (Fig.…”
Section: Jip3 Regulates Actin Dynamics At Axon Tips Through the Jnkcomentioning
confidence: 99%